Recreational Drug Use and Impulsivity in a Population of Canadian Undergraduate Drinkers - Balodis, Iris M.; Potenza, Marc N.; Olmstead, Mary C. (Frontiers in Psychiatry, 2010)
The consumption of drugs during young adulthood may be particularly detrimental given important neurodevelopmental changes occurring during this period. As impulsivity may lead to substance use and substance use to the commission of seemingly impulsive acts, an improved understanding of the relationship between alcohol use, other substance use and impulsivity in young adults is important. We gathered information on self-reported impulsivity, recreational drug use, and drinking habits of 205 (105 female) undergraduate students. Results showed that 64% of the students reported using marijuana at least once and these individuals were more likely to report binge drinking. Polydrug use, defined as using marijuana and at least one other illicit substance, was reported by 20% of students. These individuals reported more drinking occasions per month and had higher levels of trait impulsivity. Rates of recreational drug use were similar to those reported in recent national surveys, suggesting an increase in experimentation with specific illicit drugs. Given that a majority of undergraduate drinkers reported marijuana use and its association with binge drinking, future research should clarify the relationship between marijuana use and binge consumption of alcohol and prevention efforts should consider the conjoint targeting of marijuana and binge drinking. The associations between polydrug use, binge-level alcohol consumption and elevated self-reported impulsivity suggests that perceived trait impulsivity across multiple domains may predispose to excessive use of multiple substances. Longitudinal studies should examine the contribution of impulsivity to the initiation and experimentation with illicit drugs and the influence of specific substances on impulsivity.